2007
DOI: 10.1590/s0101-20612007000300018
|View full text |Cite
|
Sign up to set email alerts
|

In vitro digestibility of globulins from sapucaia (Lecythis pisonis Camb.) nuts by mammalian digestive proteinases

Abstract: Sapucaia (Lecythis pisonis Camb.) raw nuts collected from Brazil were analyzed to determine the proximate composition, amino acid profile of protein fractions, in vitro protein digestibility and antinutritional factors in order to evaluate their potential as a protein alimentary complement. The nuts contained adequate amounts of essential amino acids, fatty acids and minerals. In the present study, no hemagglutinating or inhibitory activities were observed in any of the samples investigated, indicating low or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 12 publications
2
13
0
5
Order By: Relevance
“…The biological values of the proteins of bacuri almond (raw and toasted) were close to that the proteins of sapucaia nuts (92.86%) (Denadai et al, 2007), higher than that of bocaiuva almonds (81.10 %) (Hiane et al, 2006) and baru almonds (79.43%) (Fernandes et al, 2010). As for the food efficiency coefficient (FEC) (weight gain/food intake), a significant difference between the groups (p< 0.01) was observed.…”
Section: Chemical Score Of Essential Amino Acid and Pdcaasmentioning
confidence: 51%
See 2 more Smart Citations
“…The biological values of the proteins of bacuri almond (raw and toasted) were close to that the proteins of sapucaia nuts (92.86%) (Denadai et al, 2007), higher than that of bocaiuva almonds (81.10 %) (Hiane et al, 2006) and baru almonds (79.43%) (Fernandes et al, 2010). As for the food efficiency coefficient (FEC) (weight gain/food intake), a significant difference between the groups (p< 0.01) was observed.…”
Section: Chemical Score Of Essential Amino Acid and Pdcaasmentioning
confidence: 51%
“…The extraction of oils and fats from the whole flour resulted in a flour with high content of proteins, close to that of bocaiuva almond flour (41.34%) (Hiane et al, 2006) and higher than that of baru almond (23.78%) (Fernandes et al, 2010) and sapucaia nuts (20,47%) (Denadai et al, 2007).…”
Section: Chemical Compositionmentioning
confidence: 73%
See 1 more Smart Citation
“…In almond sapucaia, Denadai et al (2007) identified the bands for globulin for 18, 34, 40 and 50 kDa. When some bands were disappeared toast, this fact can probably be attributed to the reactions occurring during the roasting process, such as Maillard complexation with polyphenolic compounds in addition to the possible formation of different polymers.…”
Section: Electrophoresis Of Isolated Fractions Of Pequi Seedsmentioning
confidence: 99%
“…Lima et al (2008) found a trypsin inhibitor in jabuticabas, with higher levels observed in seeds, followed by the peel and the entire fruit, with lower levels in the pulp and hemagglutination activity in the peel. Peptidase inhibitors and lectin were observed in almonds bacuri and seeds sapucaia (Barbosa, 2006;Denadai et al, 2007), while Hiane et al (2006) detected low concentrations of lectins and no peptidase inhibitors in bocaiuva almonds.…”
Section: Hemagglutination Activity Detection and Inhibitory For Proteasementioning
confidence: 99%